Composite Analysis of Means: Inquiry of CFO Roles, Responsibilities and Relationships in SDA North American Division Conferences - Brown Sr., Theodore (Archives of Business Research, 2017)
This examination was aroused by thoughts that perceptions of SDA Conference leadership impacts how roles, responsibilities and relationships of CFOs are viewed in terms of their understanding and working knowledge of CFO duties. Data collected in Bermuda, Canada and USA. Descriptive Statistical analysis of Means indicated significant differences among leadership perceptions.